Brief Notes: Tensile Strength of Composites Reinforced with Dispersed Fibres Determination of Reinforcement - Mianowski, K.M. (Engineering Transactions, 1997)
The title subject was analysed using the damage theory, assuming that the distribution of the fibre strength is rectangular. The derived relations can be applied for design purposes. An example of calculations is given.